2001
DOI: 10.1017/s1355838201002382
|View full text |Cite
|
Sign up to set email alerts
|

An extended structural signature for the tRNA anticodon loop

Abstract: Anticodon hairpins are structural motifs with contradictory functions. The recognition by aminoacyl synthetases implies extended interactions with the anticodon base triplet and thus, usually, an unfolding of the anticodon loop. The recognition by the ribosome and cognate interaction with a mRNA codon implies, on the other hand, the formation of a mini-helix with a canonical anticodon hairpin structure as observed by crystallography and NMR. To be able to understand the various properties of this motif, a prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 34 publications
6
62
0
1
Order By: Relevance
“…Figure 3 illustrates the results of this basic analysis and reveals that most RNA molecules show either coplanar or bipolar arrangements of their base-normal vectors. Furthermore, most tRNAs (plotted in red) exhibit a clear coplanar arrangement of their base-normal vectors in agreement with the high degree of structural conservation in this family of RNAs (Auffinger and Westhof 2001).…”
Section: Statistical Analysis Of Base-normal Vectorssupporting
confidence: 75%
“…Figure 3 illustrates the results of this basic analysis and reveals that most RNA molecules show either coplanar or bipolar arrangements of their base-normal vectors. Furthermore, most tRNAs (plotted in red) exhibit a clear coplanar arrangement of their base-normal vectors in agreement with the high degree of structural conservation in this family of RNAs (Auffinger and Westhof 2001).…”
Section: Statistical Analysis Of Base-normal Vectorssupporting
confidence: 75%
“…The mass spectrometry results (Fig+ 3 and Table S2) also showed that only the edited tRNA Trp (Um34 at the wobble position) is thiolated at U33, thus raising the question of whether thiolation precedes editing or vice versa+ To address this issue, U33 was mutated to C33, which represents the other nucleotide that almost always occurs at that position in tRNAs (Sprinzl et al+, 1998)+ In the present case, however, the mutated tRNA Trp (MASLC33) was not detectable in the mitochondrial or cytosolic fractions by RT-PCR, but was detectable in nuclear RNA, suggesting an effect either on tRNA processing or nuclear export (data not shown)+ The role (if any) that thiolation of U33 One of the most conserved structural features in tRNA is a characteristic U-turn in the anticodon loop (Auffinger & Westhof, 2001)+ This structure is maintained by subtle interactions involving hydrogen bonding, changes in sugar conformation, and base stacking between several nucleotides in the anticodon stem loop+ The interplay of structural conservation and structural variation in the anticodon stem loop is a corollary of the extended anticodon hypothesis of Yarus (1982), in which nucleotides in the upper loop and the stem expand the information content of the three anticodon nucleotides and affect the overall translational efficiency of a given tRNA+ Two models based on structural and phylogenetic analyses have been proposed for the stabilization of the U-turn structure in tRNAs+ One proposal states that a dynamic sugar puckering is essential for the formation of the universal anticodon structure (Ashraf et al+, 1999a)+ This assumes that position U33 of the anticodon is universally unmodified+ A second model maintains that formation of a bifurcated hydrogen bond between the (U33)O29 and the NH 2 and C5-H groups of C35 are more important than a dynamic sugar pucker (Auffinger & Westhof, 2001)+ Our finding that U33 is thiolated in the imported mitochondrial tRNA Trp of L. tarentolae leads to the conclusion that, whereas conformational flexibility about the sugar might be important to maintain a desirable anticodon structure for many tRNAs, this fact is not a universal feature of the anticodon structural signature+ In view of the known rigidity imparted on the sugar conformation by the presence of 2-thiouridine (Kumar & Davis, 1997;Ashraf et al+, 1999b), we speculate that at least in the case of tRNA Trp , s 2 U33 should strongly favor a C39-endo sugar conformation+ A novel tRNA editing activity or novel editing regulation?…”
Section: Editing Is Not Required For Thiolationmentioning
confidence: 51%
“…Among these, a critical hydrogen bonding pattern involves the 29 OH group of U33 and the base at position 35. The result depends on whether N35 is a purine or a pyrimidine (Auffinger and Westhof 2001).…”
Section: Degeneracy In the Genetic Code And Interpretation Of Lagerkvmentioning
confidence: 99%